Theoretical Study of the Kinetics of the Pyrolytic Elimination Reaction of Ethyl Chloride - Isaiah Ajibade Adejoro; Emmanuel Ekeh (E-Journal of Chemistry)
The products of the gas-phase elimination of ethyl chloride are hydrogen chloride and ethane. Using AM1, MNDO and PM3 Hamiltonians of quantum mechanical computer code called MOPAC, a procedure for the kinetics and computation of the Arrhenius parameters for the pyrolytic elimination reaction of ethyl chloride was devised in order to evaluate the predictive ability of the three Hamiltonians used. The first-order rate coefficient for the three Hamiltonians are 1.15x10-8s-1, 4.55x10-15s-1 and 5.36x10-4s-1 for AM1, MNDO and PM3 respectively. The results obtained showed that the rate constant for the computed Arrhenius parameters compare well with the experimental values in the literature, thus showing that the computational procedure adequately simulates experimental results; also the semi-empirical AMI calculation has the best predictive ability with experiment followed by PM3 while MNDO has the least.